STORYTELLING CASE STUDY: HOW TO WIN A TAX DISPUTE AGAINST TAX AUTHORITY? - Qadri, Resi Ariyasa; Fatmawati (Jurnal Pajak dan Keuangan Negara (PKN), 2021)
This study focuses on answering five research questions, namely how to understand the background of a tax dispute, how to carry out the tax audit, how to perform the tax audit closing conference, how to run the objection process at the regional level, and how to win the appeal process at Tax Court. This research employed the case study framework as a methodology. The data were collected via interview as well as documentation. The information gathered was analyzed by contextualizing the meaning of the data collected. The result of this research provided insights on winning a tax dispute by implementing several strategies abstracted from the case study.